The Effect of Corporate Social Responsibility, Political Connection, and Good Corporate Governance on Tax Avoidance in Mining Companies Listed on The Indonesia Stock Exchange in 2018-2023 - Romario Ananta Zalsy Dasilva; Afrizal; Misni Erwati (Greenation International Journal of Economics and Accounting, 2025)
This study aims to empirically prove the impact of corporate social responsibility, good corporate governance, and political connection on tax avoidance. The population used in this study consists of mining sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. The sample selection was carried out using purposive sampling, resulting in 78 samples of mining companies listed on the Indonesia Stock Exchange based on the sampling criteria. The data used in this study is secondary data, and the data collection method used is documentation. The data analysis method applied is multiple linear regression analysis using SPSS 25 software. The results of the study conclude that: (1) corporate social responsibility has an impact on tax avoidance, (2) good corporate governance has an impact on tax avoidance, (3) political connection has an impact on tax avoidance, and (4) the combined effect of corporate social responsibility, good corporate governance, and political connection significantly influences tax avoidance.